The Use of Le Bail Method to Analyze the Semicrystalline Pattern of a Nanocomposite Based on Polyaniline Emeraldine-Salt Form and α-Al2O3 - Edgar A. Sanches; Adriano de S. Carolino; Amanda L. dos Santos; Edson G. R. Fernandes; Daniela M. Trichês; Yvonne P. Mascarenhas (Advances in Materials Science and Engineering)
Ceramic nanocomposites constituted by a matrix of α-Al2O3 microparticles reinforced by polyaniline emeraldine-salt form (PANI-ES) nanoparticles were prepared by in situ polymerization and characterized structural and morphologically. Peaks related to both materials were observed through XRD technique: PANI-ES presented peaks at 2θ = 8.9, 14.9, 20.8, 25.3, 27.1, and 30.0° and in α-Al2O3 phase peaks were found at 2θ = 25.6, 35.2, 37.9, 43.5, 52.6, 57.6, and 68.1°. Nanocomposite crystallinity percentage was estimated around 70%. SEM showed a polymerization of PANI-ES over alumina plates. By Le Bail method it was observed that PANI-ES and α-Al2O3 have crystallite average size around, respectively, 41 and 250 Å. By FTIR analysis characteristic absorption bands of both materials were identified. Additional bands indicating new chemical bonds were not observed, suggesting that nanocomposite was formed by physical deposition. Nanocomposite DC electrical conductivity was found around 0.24 S/cm (against 1.84×10-4 S/cm for pure PANI-ES), showing an increase of about 1,300 times compared to the pure PANI-ES at room temperature. Thus, this paper showed that both materials have kept its original structural characteristics and exhibited high electrical conductivity when combined in nanocomposite form.